Computer therapy for the anxiety and depression disorders is effective, acceptable and practical health care: An updated meta-analysis - Andrews, G.; Basu, A.; Cuijpers, P.; Craske, M.; McEvoy, Peter; English, C.; Newby, J. (SAGE PUBLICATIONS LTD, 2018)
© 2018 The Authors Background: A 2010 meta-analysis of internet-delivered CBT (iCBT) RCTs argued ‘computer therapy for the anxiety and depressive disorders was effective, acceptable and practical health care’ without data on effectiveness or practicality in routine practice. Methods: Databases, reviews and meta-analyses were searched for randomised controlled trials of cCBT or iCBT versus a control group (care as usual, waitlist, information control, psychological placebo, pill placebo, etc.) in people who met diagnostic criteria for major depression, panic disorder, social anxiety disorder or generalised anxiety disorder. Number randomised, superiority of treatment versus control (Hedges'g) on primary outcome measure, length of follow-up, follow up outcome, patient adherence and satisfaction/harm were extracted; risk of bias was assessed. A search for studies on effectiveness of iCBT in clinical practice was conducted. Results: 64 trials were identified. The mean effect size (efficacy) was g = 0.80 (NNT 2.34), and benefit was evident across all four disorders. Improvement was maintained at follow-with good acceptability. Research probity was good, and bias risk low. In addition, nine studies comparing iCBT with traditional face-to-face CBT and three comparing iCBT with bibliotherapy were identified. All three modes of treatment delivery appeared equally beneficial. The results of effectiveness studies were congruent with the results of the efficacy trials. Limitations: Studies variably measured changes in quality of life and disability, and the lack of comparisons with medications weakens the field. Conclusions: The conclusions drawn in the original meta-analysis are now supported: iCBT for the anxiety and depressive disorders is effective, acceptable and practical health care.